An In Vivo Study of a Rat Fluid-Percussion-Induced Traumatic Brain Injury Model with [(11)C]PBR28 and [(18)F]flumazenil PET Imaging - Ghosh, Krishna Kanta (Int J Mol Sci, 2021)
Traumatic brain injury (TBI) modelled by lateral fluid percussion-induction (LFPI) in rats is a widely used experimental rodent model to explore and understand the underlying cellular and molecular alterations in the brain caused by TBI in humans. Current improvements in imaging with positron emission tomography (PET) have made it possible to map certain features of TBI-induced cellular and molecular changes equally in humans and animals. The PET imaging technique is an apt supplement to nanotheranostic-based treatment alternatives that are emerging to tackle TBI. The present study aims to investigate whether the two radioligands, [(11)C]PBR28 and [(18)F]flumazenil, are able to accurately quantify in vivo molecular-cellular changes in a rodent TBI-model for two different biochemical targets of the processes. In addition, it serves to observe any palpable variations associated with primary and secondary injury sites, and in the affected versus the contralateral hemispheres. As [(11)C]PBR28 is a radioligand of the 18 kD translocator protein, the up-regulation of which is coupled to the level of neuroinflammation in the brain, and [(18)F]flumazenil is a radioligand for GABA(A)-benzodiazepine receptors, whose level mirrors interneuronal activity and eventually cell death, the use of the two radioligands may reveal two critical features of TBI. An up-regulation in the [(11)C]PBR28 uptake triggered by the LFP in the injured (right) hemisphere was noted on day 14, while the uptake of [(18)F]flumazenil was down-regulated on day 14. When comparing the left (contralateral) and right (LFPI) hemispheres, the differences between the two in neuroinflammation were obvious. Our results demonstrate a potential way to measure the molecular alterations in a rodent-based TBI model using PET imaging with [(11)C]PBR28 and [(18)F]flumazenil. These radioligands are promising options that can be eventually used in exploring the complex in vivo pharmacokinetics and delivery mechanisms of nanoparticles in TBI treatment.